Impact of Air Traffic on Cirrus Coverage - Stubenrauch, C. J.; Schumann, U. (Geophysical Research Letters, 2005)
TOVS Path-B satellite data provide information on effective high cloud amount and relative humidity for the period 1987 to 1995. Differences in trends of seasonal mean effective high cloud amount between situations favorable for contrails and for cirrus are analyzed in regions with high and low air traffic density. In regions with especially high air traffic density, a significantly stronger increase of effective high cloud amount is found for situations with sufficiently cold and humid air masses favorable for contrails than for all situations in general or for situations favorable for cirrus. Situations of potential contrails occur in about 5 to 10% of all situations, and their seasonal effective high cloud amount averages lie between about 7% and 22%. Indicators of cirrus increase due to air traffic corresponding to the difference in trends of effective high cloud amount between potential contrail situations and cirrus or all situations are about 2.8%–3.5% and 1.6%–4.7% per decade over Europe and the North Atlantic flight corridor, respectively. Weighted by frequency of potential contrail occurrence, the overall increase amounts to at least 0.20%–0.25% and 0.08%–0.24% per decade over regions with very high air traffic (Europe and the North Atlantic flight corridor, respectively).